Modelo holístico: respaldo teórico para ensino de L2 e avaliação de materiais didáticos - Pinto, Cândida Martins; Braida, Fabrícia Cavichioli (Linguagens & Cidadania, 2017)
The aim of this paper is to present some relevant issues about the elaboration of materials for teaching a second language taking into account the Richter’s Holistic Model. Examples of task-based learning exercises of a class will be showed in order to give theoretical support for evaluation criterions of didactic materials.